25-hydroxyvitamin D as a predictor of reduced heart rate variability in elderly patients with diabetes mellitus - Tang, Tiantian; Sun, Xinyu; Zhang, Xiaoxiang; Li, Jiaojiao; Wang, Manjie; Hui, Cancan; Cheng, Yuwei; Kong, Xiaoming; Sun, Yan (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the risk factors for decreased heart rate variability (HRV) in elderly diabetic patients and evaluate the predictive value of 25-hydroxyvitamin D [25-(OH)D].MethodsA retrospective study was conducted, enrolling 101 elderly diabetic patients admitted to the Department of Geriatric Endocrinology at the First Affiliated Hospital of Anhui Medical University from 2023 to 2024. Patients were divided into two groups based on the standard deviation of all normal RR intervals (SDNN) from 24-hour Holter monitoring: the normal HRV group (180 ms ≥ SDNN ≥ 100 ms) and the decreased HRV group (SDNN < 100 ms). Clinical data collected included age, sex, body mass index (BMI), Diabetic peripheral neuropathy (DPN), Diabetic peripheral vascular disease (DPVD), Diabetic nephropathy (DN), Diabetic retinopathy (DR), as well as laboratory parameters such as fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), creatinine (Cr), glomerular filtration rate (GFR), uric acid (UA), cystatin C (CysC), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very-low-density lipoprotein cholesterol (VLDL-C), non-HDL-C, 25-(OH)D, 24-hour urinary total protein (24hUTP), 24-hour urinary uric acid (24hUA), microalbuminuria (MAlb), urinary albumin-to-creatinine ratio (UACR), and calculated ratios including TG/HDL-C, UA/HDL-C, and non-HDL-C/HDL-C. Statistical analyses included χ² test, independent t-test, Mann-Whitney U test, and multivariate logistic regression to identify risk factors for HRV reduction. Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive value of these factors.ResultsCompared with the normal HRV group, the decreased HRV group had significantly lower HDL-C and 25-(OH)D levels but higher prevalence of DN, along with elevated 24hUTP, MAlb, UACR, TG/HDL-C, and UA/HDL-C (all P < 0.05). These factors were identified as independent risk factors for HRV reduction in elderly diabetic patients.ConclusionThis study identified key risk factors for HRV reduction in elderly diabetic patients. Furthermore, 25-(OH)D levels may serve as an early predictive marker for decreased HRV in this population.